Seorang pendidik anak usia dini harus mengetahui model pembelajaran yang ada di paud - Narang, Umriani R. (Maliki Interdisciplinary Journal, 2025)
One of the main competencies possessed by a professional PAUD teacher or educator is the ability to decide and implement the right learning model. The learning model is a strategy chosen by a teacher to create fun and enjoyable learning. (Asrini, 2021) states that the Learning Model is an approach used for learning that is based on learning theory and psychology theory. According to the Ministry of Education and Culture in Indonesia, there are 4 learning models in PAUD, namely Classical, Group, Center and Area. The Classical Learning Model is a strategy or method in learning where learning activities are carried out at the same time and place (Fitriana et al., 2022). The Group Learning Model is an approach or learning strategy where children are divided into several groups (Putri et al., 2023). The Center Learning Model is a learning model that uses several units and makes play a learning tool for children (Khairiah & Kurinci, 2022). The Area Learning Model is a learning model that prepares children’s activities individually and in groups to develop all aspects (Rohita et al., 2022).